MUMPS MYOCARDITIS: A FORGOTTEN DISEASE? - Hussain, Sheraz; Zahid, Mohammad Faizan; Rahman, Arshalooz Jamila; Ahmed, Mehnaz Atiq; Ibrahim, Shahnaz Hamid (Journal of Ayub Medical College Abbottabad, 2016)
Mumps is an acute viral illness that follows a self-limiting course but up to 10% of cases have a complicated course with the involvement of other organ systems. Myocarditis is reported as a complication but the incidence has greatly fallen ever since the development of the mumps vaccine. A child presented to our department with parotid swelling and fever. Persistent tachycardia with irregular pulse led to further cardiac work up which showed decreased ejection fraction and raised serum cardiac enzymes, indicating myocardial damage. With ionotropic agents and supportive care, there was complete normalization of ejection fraction and serum cardiac enzyme levels. He was discharged within a week of admission. This case highlights the importance of suspecting myocarditis in the setting of mumps, a diagnosis that precludes early suspicion in mumps patients suffering from cardiac symptoms not explained by other potential aetiologies. Early suspicion and timely supportive care are essential to ensure favourable outcomes.